Reinterpreting Arthurian characters: A comparative characterization analysis of Le Morte d'Arthur (1485) and The Kid Who Would Be King (2019) - Achmad Vyan Krisnandha; Yasmin Farani (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2026)
Literary adaptations frequently reinterpret characters to meet the expectations of new audiences while preserving key elements of the source text. This qualitative study examines the characterization of Arthurian characters in Sir Thomas Malory's Le Morte d'Arthur (1485) and Joe Cornish's The Kid Who Would Be King (2019), compares their portrayals, and explains their reinterpretation using Linda Hutcheon's adaptation theory. A qualitative comparative approach was employed to analyze three corresponding character pairs King Arthur/Alex, Merlin/Merlin, and Morgan le Fay/Morgana through Roberts' characterization framework, which considers characters' speech and thoughts, actions, others' perspectives, and authorial presentation. The findings reveal that the film largely preserves the characters' fundamental narrative functions while adapting their characterization to suit contemporary audiences. King Arthur and Alex are consistently portrayed as brave and responsible leaders, Merlin remains a wise mentor figure despite a more approachable personality, and Morgan le Fay and Morgana continue to function as central antagonists with different modes of villainy. These findings demonstrate that the adaptation maintains the core identities of Arthurian characters while reinterpreting their characterization within a modern cinematic context, contributing to broader discussions of literary adaptation and character transformation.